PELAKSANAAN RETENSI PADA MASA PERALIHAN REKAM MEDIS MANUAL KE REKAM MEDIS ELEKTRONIK ( RME ) DI KLINIK UTAMA CAHAYA QALBU - Salsabilah Putri; Erix Gunawan (Media Bina Ilmiah, 2022)
Medical recorders at the Cahaya Qalbu Main Clinic Health Facility are conducting retention activities that coincide with the transition from manual medical records to electronic medical records (RME). With limited human resources (HR) at the clinic, there was a delay in shrinking medical record documents. Coupled with a medical record system that is still manual, medical recorders require a lot of manpower and more space to store forms. The importance of holding retention in the management of medical records, one of which is to maintain the neatness of the preparation of active medical records and reduce the increasing number of medical records. This study aims to analyze the results of the implementation of the retention of a medical record system that is still manual to become an electronic medical record. The method used is descriptive method with a qualitative approach. This research is done by analyzing the surrounding events, and interviewing the medical record officer at the clinic. The suggestions given are: (1) Medical recorders need to immediately complete retention activities so that further retention activities can be carried out with an electronic or computerized medical record system. (2) The need for additional human resources for medical recorders to reduce the workload.